THE INFLUENCE OF USE MATHEMATICS FRACTION BOARD LEARNING MEDIA AND PARENTAL ATTENTION ON MOTIVATION FOR LEARNING MATHEMATICS - Sobariah, Laely; Amaliyah, Nurrohmatul; Purwanto, Sigid Edy (EDUPEDIA, 2024)
The purpose of this research were: 1)to determine the influence of learning media on motivation in learning mathematics; 2) to know the influence between parental attention and motivation in learning mathematics, and; 3) to understand the influence between mathematics learning media and parents' attention to motivate students in learning mathematics. This research is a quasi-experimental research with a quantitative approach. The research method used is analysis of variance (ANOVA) using a simple factorial design (2x2) and post hoc test of Dunnet Test. The population and sample used in this study were class III students at Dukuh 05 Pagi Elementary School. The instrument used in this study was in the form of a questionnaire containing statements using the Likert scale parameter. Based on the analysis that has been done, the researchers found that there was an influence between mathematics learning media and parents' attention to the motivation to learn mathematics. This can be seen from the results of the ANOVA test which showed a value higher than 4.047 (Fh of the 0.05 significance level) which were 14.14 on the learning media variable, 59.98 on parental attention, and 12.71 on the interaction between the two on motivation to learn mathematics. Researchers also found that there was interaction between variables in the Dunnet Test with parents' attention playing the highest role in influencing students' motivation to learn mathematics.